S(Ns)= Ns - N taking the denominator of the RHS to LHS

S(Ns) - Ns = -N (taking Ns to the LHS from RHS)

Ns - S(Ns) = N (rearranging the terms to make N on the RHS positive)

Ns (1 - S) = N (rearranging the LHS)

Therefore,

Ns = N / (1-S).

]]>As long as S=1-1/s, no matter what N is ,the equation S = (Ns - N) / (Ns)

is valid. That means N is Undetermined by this equation! (N can be any number)

another example a+2N=a+N+N, can you solve N out?

]]>I need to re-arrange the following formula in way so i can get Ns on its own!!!!

S = (Ns - N) / (Ns)

So as i said, i cant get Ns on its own!!!! WOuld be greatful if anyone could help!!!!

]]>